Testing agent for rapidly distinguishing true and false inorganic coating, preparation method and testing method
By preparing test agents containing calcium chloride, quartz powder and hardener, using the reaction characteristics of inorganic silicates and the calcium ion stability differences of synthetic resin emulsions, we can accurately distinguish between true and false inorganic coatings within 4 hours, and solve the problem of solving the problem of using inorganic silicate reaction characteristics and differences in calcium ion stability of synthetic resin emulsions. The problem of inaccurate and inconvenient identification in the prior art is provided, and a fast, simple and suitable identification method is provided for multiple occasions.
Patent Information
- Application Number
- CN202310686883.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-13
AI Technical Summary
The prior art cannot accurately and quickly identify authentic and false inorganic coatings, resulting in market chaos, and traditional methods such as odor, pH value and ash method have problems such as inaccurate or inconvenient.
Prepare a test agent including pure water, calcium chloride, quartz powder and hardener, and quickly distinguish by mixing specific proportions and sequences using the reaction characteristics of inorganic silicates and the calcium ion stability differences of synthetic resin emulsions. The curing conditions of inorganic coatings and latex paints provide a fast and simple identification method.
It realizes accurate distinction between real and fake inorganic coatings within 4 hours, breaks away from the dependence of laboratory equipment, is suitable for more occasions, and provides a fast, convenient and accurate identification method.
Smart Images

Figure CN119125512A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of testing of inorganic coatings, and in particular to a testing agent, a preparation method and a testing method for quickly distinguishing true from false inorganic coatings. Background Art
[0002] Inorganic coatings use inorganic silicates as the main film-forming material. After being applied to the surface of mineral substrates such as concrete and cement, they penetrate into the substrate surface and undergo a silicification reaction to form a film, forming a waterproof and acid-proof hard silica surface coating, which can protect and decorate the surface of the building. Latex paint, on the other hand, is formed by the volatilization of water, the accumulation and deformation of latex particles, and the aggregation of organic synthetic resin emulsions to form a film. Due to the difference in film-forming materials, inorganic coatings have excellent properties such as flame resistance, natural environmental protection, mildew resistance and antibacterial, and hard paint film compared to latex paint. At present, the domestic standard for inorganic coatings, "JG / T26-2002 Inorganic Building Coatings for External Walls", is not a very accurate and detailed standard for inorganic coatings. Latex paints with excellent performance can also meet the technical indicators required by the above standards, resulting in some of the inorganic coatings currently on the market being packaged from ordinary latex paints, and some "inorganic coatings" obtained by using silica sol compounded with polymer organic emulsions, and the actual physical and chemical properties they show are also organic coatings. Therefore, the inorganic coatings market is also somewhat chaotic, and it is particularly important to find a simple, fast and accurate method to identify genuine and fake inorganic coatings.
[0003] At present, the identification methods of inorganic coatings in China mainly include odor identification, pH value identification, and ash identification according to the different characteristics of their respective film-forming materials. The development and application of odorless emulsions and alkali-resistant emulsions have made odor and pH value identification no longer accurate; the high-temperature calcination relies on testing instruments, which makes the ash method not convenient and fast. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a test agent, preparation method and test method for quickly distinguishing true and false inorganic coatings, which can quickly, simply and accurately distinguish true and false inorganic coatings. The present invention is based on the reaction characteristics of inorganic silicates in the film-forming process, and at the same time improves the curing speed (the reaction of inorganic film-forming materials is relatively slow, especially when contained in a container, it may take about a month to achieve complete curing. Therefore, in order to achieve the purpose of rapid curing of the test agent, a hardening accelerator must be used), and prepares a test agent that can react and cure quickly with inorganic silicates, but has no effect on latex paint or will destroy the film formation of the emulsion, and then uniformly mixes with the test sample paint according to a specific method and proportion, and distinguishes true and false inorganic coatings through the curing conditions for a certain period of time.
[0005] To solve the above problems, the present invention is implemented through the following technical solutions:
[0006] The first invention object of the present invention is:
[0007] A test agent for quickly distinguishing true from false inorganic coatings is provided, which comprises the following components in weight percentage:
[0008] Pure water 10-30%, calcium chloride 0.1-5%, quartz powder 5-25%, hardening accelerator 55-85%, the sum of all components is 100%.
[0009] A preferred example of the test agent for quickly distinguishing true from false inorganic coatings of the present invention is:
[0010] The calcium chloride is anhydrous calcium chloride.
[0011] A preferred example of the test agent for quickly distinguishing true from false inorganic coatings of the present invention is:
[0012] The hardening accelerator is sodium fluorosilicate.
[0013] A preferred example of the test agent for quickly distinguishing true from false inorganic coatings of the present invention is:
[0014] The quartz powder is one or a combination of 400 mesh, 800 mesh and 1250 mesh.
[0015] A preferred example of the test agent for quickly distinguishing true from false inorganic coatings of the present invention is:
[0016] Add the raw material components mentioned above into the mixing tank in accordance with the formula ratio and order (from top to bottom in the formula table) and stir evenly. Note that when adding calcium chloride, the remaining materials should be added only after the calcium chloride is completely dissolved, and finally the test agent is obtained.
[0017] The second object of the present invention is:
[0018] A method for preparing the test agent for quickly distinguishing true from false inorganic coatings is provided. The raw material components are added into a mixing tank in sequence according to the formula ratio and order (from top to bottom in the formula table) and stirred evenly. Note that when adding calcium chloride, the remaining materials should be added only after the calcium chloride is completely dissolved, and finally the test agent is obtained.
[0019] The third invention object of the present invention is:
[0020] Provide a test method for quickly distinguishing true and false inorganic coatings using a test agent, taking the mass M b The test sample paint with mass M a Test agent, mix and stir evenly, record the time, and observe the curing condition within 4 hours;
[0021] Among them, M b :M a =2:1.
[0022] A preferred example of the testing method of the present invention using a testing agent for quickly distinguishing true from false inorganic coatings is:
[0023] Mix the test sample paint and the test agent and stir evenly for 4 hours to observe the curing condition:
[0024] The inorganic coating solidifies to form a hard block;
[0025] The viscosity and curing conditions of ordinary latex paints do not change significantly or the paint breaks down into a bean curd-like state and no longer forms a film and solidifies.
[0026] The test method for quickly distinguishing true from false inorganic coatings of the present invention has the following distinguishing mechanism between the test sample paint and the test agent:
[0027] a. Ordinary latex paint (synthetic resin emulsion) has poor calcium ion stability. The addition of excessive calcium chloride will cause the latex paint to break and coagulate. The content of calcium chloride can adjust the sensitivity of distinguishing true and false inorganic coatings.
[0028] b. Inorganic coating (alkali metal silicate) solidifies with quartz powder
[0029] M2O.nSiO2+mSiO2→M2O.(m+n)SiO2
[0030] Alkali metal silicate quartz powder Alkali metal silicate with higher modulus
[0031] c. Reaction of inorganic coatings (alkali metal silicates) with polyvalent metal ions
[0032]
[0033] The purpose of the present invention is to provide a test agent, preparation method and test method for quickly distinguishing true and false inorganic coatings, which can break away from the constraints of laboratory equipment and be applied to more occasions. The design concept of the method is:
[0034] According to the different film-forming materials of inorganic coatings and latex paints, and based on the reaction mechanism of inorganic silicates and the calcium ion stability of synthetic resin emulsions, an identification test agent is formulated that will only react with inorganic silicates and will demulsify the synthetic resin emulsion. The test agent is then mixed with the identification sample paint in a specific ratio (sample paint: test agent = 2:1) to react, and its curing condition is observed in a short time to identify and distinguish genuine and fake inorganic coatings.
[0035] The present invention is a test method for quickly distinguishing true and false inorganic coatings, while taking into account the advantages of various common test methods: convenient, fast, and accurate. This test method mainly configures an identification test agent that only reacts with inorganic silicates, reacts excessively with the inorganic film-forming material of the test sample paint, and distinguishes true and false inorganic coatings by observing the degree of curing of the sample paint after the reaction. This identification method is not only suitable for testing and identification in the laboratory, but also more convenient for identification and detection by users, project sites, etc. when there are no experimental instruments. It does not require the use of laboratory equipment such as muffle furnaces and constant temperature drying ovens, and can obtain identification results within 4 hours. It is fast, convenient and accurate. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a comparison chart of the test results of Example 1 of the present invention.
[0037] Figure 2 This is a comparison chart of the test results of Example 2 of the present invention.
[0038] Figure 3 This is a comparison chart of the test results of Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0039] In order to make the application, technical scheme and advantages of the present invention clearer, the present invention is described in detail in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not limited to the present invention. All simple improvements to the preparation method of the present invention under the premise of the present invention are within the protection scope of the present invention.
[0040] Example 1
[0041] A test method for quickly distinguishing true from false inorganic coatings using a test agent (the test agent involved in the present invention is prepared by a normal process, and the formula table is added from top to bottom in sequence. Note that the calcium chloride should be completely dissolved before adding the next step of materials)
[0042] It includes the following steps:
[0043] (1) Test agent configuration, the raw materials and weight percentages of each component are as follows:
[0044] raw materials Mass percentage (%) Pure water 20 Calcium chloride 0.1 Quartz powder 14.9 Hardening accelerator (sodium fluorosilicate) 65
[0045] (2) Configure the quality to M a Test agent (add according to the order in the table, add the next raw material after calcium chloride is completely dissolved);
[0046] (3) Take the mass as M b The test sample paint with mass M a Test agent (M b :M a=2:1) Stir evenly, record the time, and observe the curing situation within 4 hours;
[0047] The test coating was mixed with the test agent according to the above scheme and left for 4 hours to observe the curing condition:
[0048] Inorganic coatings solidify to form hard blocks ( Figure 1 in the right figure);
[0049] The viscosity and curing of ordinary latex paints have no obvious changes or the emulsion breaks into a bean dregs state and no longer forms a film and solidifies ( Figure 1 , left figure).
[0050] The addition of calcium chloride, three key components in the test agent, utilizes the principle that the calcium ion stability of synthetic resin emulsion is poor. When the calcium ion concentration reaches a certain level, the latex paint breaks into a bean dregs state and loses its film-forming property, while the inorganic film-forming material is not affected but solidifies instead; the addition of quartz powder and sodium fluorosilicate ensures the reaction of the inorganic film-forming material and the improvement of the reaction speed, and the film-forming and curing can be completed in a short time. Thus, the two can be quickly distinguished. Therefore, the test agent formula of the above embodiment 1 achieves the purpose and requirements of the test agent.
[0051] Example 2
[0052] A test method for quickly distinguishing true and false inorganic coatings using a test agent (based on Example 1, adjusting the test sensitivity of the test agent, that is, adjusting the proportion of calcium chloride and hardening accelerator in the test agent formula, can make the latex paint demulsify faster and the inorganic coating cure faster, thereby obtaining the test result faster)
[0053] It includes the following steps:
[0054] (1) Test agent configuration, the raw materials and weight percentages of each component are as follows:
[0055] raw materials Mass percentage (%) Pure water 21 Calcium chloride 0.4 Quartz powder 5 Hardening accelerator (sodium fluorosilicate) 73.6
[0056] (2) Configure the quality to M a Test agents (add in the order of the table, add the next raw material after calcium chloride is completely dissolved);
[0057] (3) Take the mass as M b The test sample paint with mass M a Test agent (M b :M a =2:1) Stir evenly, record the time, and observe the curing situation within 4 hours;
[0058] After mixing the test agent according to the above scheme, the test coating:
[0059] Initial situation:
[0060] The viscosity of ordinary latex paint increases rapidly, demulsifies into bean dregs, and the plastic cup does not heat up ( Figure 2 Left 1)
[0061] The viscosity of the inorganic coating gradually thickens, the curing reaction gradually begins, and the plastic cup becomes noticeably hot ( Figure 2 Left 2)
[0062] Mix and place for 2 hours:
[0063] Ordinary latex paint is still in the form of broken bean dregs and no longer forms a film and solidifies ( Figure 2 3) on the left.
[0064] Inorganic coatings solidify to form hard blocks ( Figure 2 4 on the left).
[0065] Adjustment of the proportion of key components in the test agent: the proportion of calcium chloride is increased to 0.4%, making the latex paint demulsification faster and more obvious; the proportion of hardening accelerator sodium fluorosilicate is increased to 73.6%, and the inorganic film-forming material reacts and cures faster and more violently; after adding the test agent of this formula to the two coatings, a huge difference can be produced in a shorter time, and the distinction is more obvious. Calcium chloride and sodium fluorosilicate are the key raw materials for adjusting the sensitivity of the test agent. Different proportions will directly affect the test time and even produce different test results. Therefore, the test agent formula of Example 2 above achieves the purpose and requirement of the test agent to improve the test sensitivity.
[0066] Comparative Example 1
[0067] A testing method for quickly distinguishing true from false inorganic coatings using a testing agent (the raw materials of the testing agent are not added according to the process sequence of the present invention, that is, calcium chloride is added last or the calcium chloride is not fully dissolved)
[0068] It includes the following steps:
[0069] (1) Test agent configuration, the raw materials and weight percentages of each component are as follows:
[0070] raw materials Mass percentage (%) Pure water 20 Quartz powder 14.9 Hardening accelerator (sodium fluorosilicate) 65 Calcium chloride 0.1
[0071] (2) Configure the quality to M a Test agent (add according to the order in the table, calcium chloride is added last, at this time the test agent is viscous and calcium chloride is difficult to dissolve);
[0072] (3) Take the mass as M b The test sample paint with mass M a Test agent (M b :M a =2:1) Stir evenly, record the time, and observe the curing situation within 4 hours;
[0073] The test coating was mixed with the test agent according to the above scheme and left for 4 hours to observe the curing condition:
[0074] Inorganic coatings solidify to form hard blocks ( Figure 3 in the right figure);
[0075] Ordinary latex paint also solidifies (no signs of demulsification), but its hardness is weaker than that of inorganic paint, and the difference between the two is not clear enough ( Figure 3 , left figure).
[0076] When calcium chloride, the key component of the test agent, was added last, it was very viscous and only dissolved a small amount, so the key component for distinguishing latex paint did not work, and no demulsification occurred. Eventually, as time went on, latex paint and inorganic coatings solidified to varying degrees, resulting in unclear results and unclear distinction.
[0077] To sum up, the embodiments of the present invention are only preferred examples of the present invention and do not limit the present invention in any form. Any equivalent changes made by technicians familiar with the profession without departing from the scope of the technical solution of the present invention using the disclosed technical content are regarded as equivalent examples of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.
[0078] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0079] The experimental methods without specific conditions in the present invention are usually carried out under conventional conditions or conditions recommended by the manufacturer.
[0080] Unless otherwise stated, the various optimization technical solutions in the present invention can be combined with each other.
[0081] Unless otherwise indicated, percentages and parts are by weight.
[0082] Experimental methods without specific conditions specified in the instructions and examples are usually carried out under conventional conditions or conditions recommended by the manufacturers.
[0083] Unless otherwise defined, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention.
Claims
1. A test agent for quickly distinguishing true from false inorganic coatings, characterized by: It includes the following components in weight percentage: Pure water 10-30%, calcium chloride 0.1-5%, quartz powder 5-25%, hardening accelerator 55-85%, the sum of all components is 100%.
2. The test agent for quickly distinguishing true from false inorganic coatings according to claim 1, characterized in that: The calcium chloride is anhydrous calcium chloride.
3. The test agent for quickly distinguishing true from false inorganic coatings according to claim 1, characterized in that: The hardening accelerator is sodium fluorosilicate.
4. The test agent for quickly distinguishing true and false inorganic coatings according to claim 1, characterized in that: The quartz powder is one or a combination of 400 mesh, 800 mesh and 1250 mesh.
5. The method for preparing a test agent for quickly distinguishing true from false inorganic coatings according to any one of claims 1 to 4, characterized in that: Add the raw material components in the mixing tank in order according to the formula ratio and sequence, and stir evenly to obtain the test agent.
6. The method for preparing a test agent for quickly distinguishing true from false inorganic coatings according to claim 5, characterized in that: The raw material components are added into a mixing tank in order according to the formula ratio and sequence and stirred evenly. When adding calcium chloride, the remaining materials should be added only after the calcium chloride is completely dissolved to obtain a test agent.
7. A testing method using a testing agent for quickly distinguishing true from false inorganic coatings, characterized in that: Take the mass as M b The test sample paint with mass M a Test agent, mix and stir evenly, record the time, and leave for 4 hours to observe the curing condition; Among them, M b :M a =2:
1.
8. The testing method using a testing agent for quickly distinguishing true from false inorganic coatings according to claim 7, characterized in that: Mix the test sample paint and the test agent and stir evenly for 4 hours to observe the curing condition: The inorganic coating solidifies to form a hard block; The viscosity and curing conditions of ordinary latex paints do not change significantly or the paint breaks down into a bean curd-like state and no longer forms a film and solidifies.
